The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1464-410x.2001.02394.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular tumour rejection mechanisms in the peritumoral bladder wall after bacillus Calmette‐Guérin treatment

Abstract: Objective To compare the immunological status of normal and peritumoral bladder walls, and to characterize immunocompetent cells before and during intravesical instillations of bacillus Calmette-Gue Ârin (BCG). Patients and methods Twenty-three patients with super®cial urothelial bladder carcinoma (stages pTa to pT1, grades 1±3) were treated with six weekly instillations of 150 mg of BCG (Pasteur strain). Biopsies of cystoscopically normal bladder wall were taken before, 3 weeks and 3 months after BCG instilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
3
33
0
1
Order By: Relevance
“…BCG instillation has been proposed to overcome the tolerance established in the tumor, and switch the immune system towards effective antitumor activity (Saint et al, 2001). Jinushi et al (Jinushi et al, 2007) have shown that, in the presence of pathogen-derived ligands and/or necrotic cells, phagocytosis of tumor cells by macrophages is performed in the absence of Mfge8 and results in effective anti-tumor immune responses, whereas in the absence of these stress conditions, the same phagocytosis performed through Mfge8 induces tolerogenic immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…BCG instillation has been proposed to overcome the tolerance established in the tumor, and switch the immune system towards effective antitumor activity (Saint et al, 2001). Jinushi et al (Jinushi et al, 2007) have shown that, in the presence of pathogen-derived ligands and/or necrotic cells, phagocytosis of tumor cells by macrophages is performed in the absence of Mfge8 and results in effective anti-tumor immune responses, whereas in the absence of these stress conditions, the same phagocytosis performed through Mfge8 induces tolerogenic immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that macrophages actively mediate BCG's anti-bladder cancer activity. Following BCG instillation, increased numbers of macrophages, along with T cells, natural killer (NK) cells and dendritic cells (DC), are observed in bladder cancer infiltrates and the peritumoral bladder wall [4,[7][8][9][10]. The voided urine of bladder cancer patients after BCG treatment also contains increased numbers of macrophages and other types of immune cells [11][12][13].…”
Section: Introductionc Ei_4105 359368mentioning
confidence: 99%
“…As a result of intravesical administration of BCG increased numbers of granulocytes and mononuclear cells including macrophages, T cells, natural killer (NK) cells and dendritic cells (DC) infiltrate the bladder wall [8,[17][18][19]. Large amounts of immune cells [20,21] and secreted cytokines are also detected in the urine after intravesical BCG administration [22].…”
Section: Discussionmentioning
confidence: 99%